FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA SEMARANG - Setyowati, Lilis; Isthika, Wikan; Pratiwi, Ririh Dian (KINERJA, 2016)
AbstractThe purpose of this study is analyze the factors influence the quality of financial statement .This study uses primary data obtained from questionnaires to accounting of SKPD Semarang. The method used in this research is multiple regression analysis. The results of this study indicate that (1) the variable role of information technology did not significantly affect the quality of financial statements, (2) the competence of human resources significant positive effect on the quality of financial statements, (3) the role of internal audit significant positive effect on the quality of financial statements.Keywords: role of IT, competence of human resources, role of internal audit, and quality of financial statement